2017
DOI: 10.1186/s13256-017-1473-2
|View full text |Cite
|
Sign up to set email alerts
|

Paraganglioma in the bladder: a case report

Abstract: BackgroundParaganglioma is an extra site of pheochromocytoma. Paraganglioma in the bladder is a very rare disease accounting for 0.06% of all bladder tumors.Case presentationA 77-year-old Japanese man was referred to our department for the further examination of a bladder tumor detected on preoperative computed tomography of his gastric cancer. Cystoscopy revealed a submucosal tumor in the upper area of his bladder, so transurethral resection of the bladder tumor was performed. During transurethral resection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Non-functional bladder paragangliomas can be easily misdiagnosed as bladder cancer before surgery, especially for those with gross hematuria as main complaint. It is reported that only 28.9% of bladder paraganglioma were successfully diagnosed before surgery, and 61.6% were initially suspected as bladder cancer or intramucosal bladder tumor (15). No.…”
Section: Discussionmentioning
confidence: 99%
“…Non-functional bladder paragangliomas can be easily misdiagnosed as bladder cancer before surgery, especially for those with gross hematuria as main complaint. It is reported that only 28.9% of bladder paraganglioma were successfully diagnosed before surgery, and 61.6% were initially suspected as bladder cancer or intramucosal bladder tumor (15). No.…”
Section: Discussionmentioning
confidence: 99%
“…Iwamoto et al . reported sharp fluctuations in blood pressure at the start of TUR for paraganglioma of the bladder . Recently, laparoscopic or robot‐assisted laparoscopic partial cystectomy has become the most commonly reported treatment for patients with paraganglioma of the bladder .…”
Section: Discussionmentioning
confidence: 99%
“…Iwamoto et al reported sharp fluctuations in blood pressure at the start of TUR for paraganglioma of the bladder. 7 Recently, laparoscopic or robot-assisted laparoscopic partial cystectomy has become the most commonly reported treatment for patients with paraganglioma of the bladder. 6,8,9 In comparison with open surgery, laparoscopic surgery offers the following advantages: minimally invasive, faster recovery, and shorter hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Editorial Comment to Functional paraganglioma of the bladder: Both radiographicnegative and laboratory-negative case Cases of pheochromocytoma of the urinary bladder are quite rare, accounting for 0.05% of bladder tumors and less than 1% of all pheochromocytomas. 1 Pheochromocytomas are clinically important, and functional tumors have been reported by Zhai et al 2 to account for over 63.6% of cases of paraganglioma in the bladder. Clinicians must be vigilant for signs of severe hypertension subsequent to the surgical procedure, which can result in fatal outcomes such as intracranial hemorrhage.…”
Section: Conflict Of Interestmentioning
confidence: 99%